Porous lithium-doped hydroxyapatite scaffold seeded with hypoxia-preconditioned bone-marrow mesenchymal stem cells for bone-tissue regeneration. (6th June 2018) - Li, Donghai; Huifang, Liu; Zhao, Jinhai; Yang, Zhouyuan; Xie, Xiaowei; Wei, Zhun; Li, Dongzhe; Kang, Pengde
Abstract: Hydroxyapatite (HA) is a commonly used biomaterial in bone-tissue engineering, but pure HA is deficient in osteoinduction. In this study, we fabricated scaffolds of lithium-doped HA (Li-HA) and assess the bone generation enhancement of Li-HA scaffolds seeded with hypoxia-preconditioned bone-marrow mesenchymal stem cells (BMMSCs). We found that 1.5%Li-HA obtained optimal cell proliferation activity in vitro . In an in vivo study, Li-HA/BMSCs enhanced new bone formation, reducing the GSK-3 β and increasing the β -catenin, but the angiogenic effect was not modified significantly. However, when the seeded BMMSCs had been preconditioned in hypoxia condition, the new bone formation was increased, with lower GSK-3 β and higher β -catenin amounts detected. The HIF-1 α secretion was up-regulated, and the vascular endothelial growth factor and CD31 expression increased. In conclusion, the bone scaffold developed from Li-doped HA seeded with hypoxia-preconditioned BMMSCs exerted positive effect on activating the Wnt and HIF-1 α signal pathway, and showed good osteogenesis and angiogenesis potential. The composited scaffold contributed to an encouraging result in bone regeneration.